Microbial N-cycling gene abundance is affected by cover crop specie and development stage in an integrated cropping system - Rocha, Kassiano Felipe [UNESP]; Kuramae, Eiko Eurya; Ferrari Borges, Beatriz Maria; Leite, Marcio Fernandes Alves; Rosolem, Ciro Antonio [UNESP] (Springer, 2020)
Grasses of the Urochloa genus have been widely used in crop-livestock integration systems or as cover crops in no-till systems such as in rotation with maize. Some species of Urochloa have mechanisms to reduce nitrification. However, the responses of microbial functions in crop-rotation systems with grasses and its consequence on soil N dynamics are not well-understood. In this study, the soil nitrification potential and the abundance of ammonifying microorganisms, total bacteria and total archaea (16S rRNA gene), nitrogen-fixing bacteria (NFB, nifH), ammonia-oxidizing bacteria (AOB, amoA) and archaea (AOA, amoA) were assessed in soil cultivated with ruzigrass (Urochloa ruziziensis), palisade grass (Urochloa brizantha) and Guinea grass (Panicum maximum). The abundance of ammonifying microorganisms was not affected by ruzigrass. Ruzigrass increased the soil nitrification potential compared with palisade and Guinea grass. Ruzigrass increased the abundance of N-fixing microorganisms at the middle and late growth stages. The abundances of nitrifying microorganisms and N-fixers in soil were positively correlated with the soil N-NH4+ content. Thus, biological nitrogen fixation might be an important input of N in systems of rotational production of maize with forage grasses. The abundance of microorganisms related to ammonification, nitrification and nitrogen fixing and ammonia-oxidizing archea was related to the development stage of the forage grass.
Keywords: Ammonia-oxidizing archaea; Ammonia-oxidizing bacteria; Guinea grass; Nitrification inhibition; Palisade grass